1991
DOI: 10.1111/j.1365-2796.1991.tb00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Treating insulin resistance in hypertension with metformin reduces both blood pressure and metabolic risk factors

Abstract: Insulin resistance and hyperinsulinaemia may play an important role in both the development of hypertension and its accompanying metabolic aberrations. In order to investigate this possibility, nine non-obese, non-diabetic, non-smoking, middle-aged men with untreated hypertension were treated with metformin 850 mg b.i.d. for 6 weeks as a pilot study and within-patient comparison. Metformin decreased total and LDL-cholesterol (P less than 0.01), triglyceride (P less than 0.01), fasting plasma insulin (P less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
7
5

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(107 citation statements)
references
References 28 publications
9
86
7
5
Order By: Relevance
“…Thus, we were neither able to support nor rule out the previously suggested beneficial effect of metformin on BP in insulin-resistant hypertensives [6] or obese female subjects [7].…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Thus, we were neither able to support nor rule out the previously suggested beneficial effect of metformin on BP in insulin-resistant hypertensives [6] or obese female subjects [7].…”
Section: Discussioncontrasting
confidence: 96%
“…Studies of the effect of metformin on blood pressure in NIDDM patients are not conclusive [5]. In most studies of the effect in nondiabetic subjects [6][7][8][9], both plasma insulin and blood pressure (BP) are reduced. Especially in the pilot study of Landin et al [6], a large reduction of BP was observed during metformin treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46][47] Treating insulin resistance with metformin reduces together the glucose disposal in response to insulin and the altered fibrinolytic activity. 48,49 In the present study, although insulin and PAI antigen were significantly correlated, it seems likely that both insulin and PAI antigen influenced the ABI ratio, but only insulin played a significant role in treated subjects. Since the population was treated by various antihypertensive agents, further studies are needed to clarify the druginduced links between the ABI and PAI antigen.…”
Section: The Abi Ratio and Plasma Insulincontrasting
confidence: 50%
“…Landin et al 54 reported that 6 weeks of oral administration of metformin, a biguanide, to insulin-resistant, hypertensive men increased insulin sensitivity and significantly decreased arterial pressure (e.g., diastolic pressure fell by -24±5 mm Hg). The authors emphasized that this was a pilot, uncontrolled study.…”
Section: Interaction Of Hyperinsulinemia Insulinmentioning
confidence: 99%